The effects of vest type dynamic elastomeric fabric orthosis on sitting balance and gross manual dexterity in children with cerebral palsy: a single-blinded randomised controlled study*. Issue 3 (30th January 2020) - Giray, Esra; Karadag-Saygi, Evrim; Ozsoy, Tugba; Gungor, Sabiha; Kayhan, Onder
Abstract: Purpose: To evaluate the effects of vest type dynamic elastomeric fabric orthosis on posture and balance during sitting and gross manual dexterity and to compare the efficacy of daily wearing time of 2 h versus 6 h. Method: Twenty-four children with cerebral palsy (CP) aged 3–9 years with GMFCS levels III and IV were randomised to either of three groups: (i) a control group who received only conventional exercise therapy, (ii) dynamic elastomeric fabric orthosis 2 h group who wore the orthosis for 2 h during therapy and dynamic elastomeric fabric orthosis 6 h group who wore the orthosis for 4 h in addition to the 2 h of wear along with therapy during hospital inpatient stay for 2 weeks. Children continued to use dynamic elastomeric fabric orthosis during the post-discharge period. The primary outcome measure was the Sitting Assessment Scale. The secondary outcome measurements were the sitting dimension of Gross Motor Function Measure, Box and Block Test and Parent Satisfaction Survey. Assessments were made before treatment, at post-treatment, at 1-month post-treatment, and at 3-months post-treatment. Sitting Assessment Scale and Box and Block Test were also assessed when immediately after wearing the orthosis. This trial is registered with Clinicaltrials.gov, under number NCT03191552. Results: All groups showed similar improvements except the control group which showed less improvement in Sitting Assessment Scale scores compared to the dynamic elastomeric fabric orthosis groups. Dynamic elastomeric fabric orthosis groups showed greater improvements compared to the control group in the Sitting Assessment Scale but not in the sitting dimension of Gross Motor Function Measure and Box and Block Test at post-treatment, at 1-month post-treatment and at 3-months post-treatment. When the dynamic elastomeric fabric orthosis groups (2 h versus 6 h) were compared, there were no significant differences in any of the assessments. The Sitting Assessment Scale and Box and Block Test scores also improved immediately after the patients put on the orthosis. At 1-month post-treatment, parents of children in the control group reported less satisfaction than parents of the children in dynamic elastomeric fabric orthosis groups. Conclusions: Dynamic elastomeric fabric orthosis vest has an immediate effect on the sitting balance and gross manual dexterity. It also provides improvements in posture and balance during sitting. Wearing dynamic elastomeric fabric orthosis vest for 2 h during therapy is as much effective as wearing it for 6 h in children with CP in addition to therapy to improve sitting balance. Implications for rehabilitation: Dynamic elastomeric fabric orthosis vest provides improvements in sitting balance when used in addition to conventional therapy in children with cerebral palsy. Wearing dynamic elastomeric fabric orthosis for 2 h and wearing dynamic elastomeric fabric orthosis vest for 6 h resulted in similar clinical outcomes. Dynamic elastomeric fabric orthosis vest has an immediate effect on sitting balance and gross manual dexterity in children with cerebral palsy.